Gastrointestinal Dysfunction in Children With Autism Spectrum Disorders. Issue 4 (21st April 2014) - Kang, Victor; Wagner, George C.; Ming, Xue
<x xml:space="preserve">Abstract</x> Gastrointestinal (GI) dysfunctions are frequently reported by parents of children with autism spectrum disorders (ASD) and have been recently recognized as a comorbid condition. However, the clinical significance of these GI dysfunctions remains to be delineated. This study describes the clinical characteristics, associated comorbid disorders, and endoscopic and colonoscopic evaluation of GI dysfunction in a cohort of 164 children with ASD evaluated at a pediatric neurology practice. Symptoms of GI dysfunction were prevalent: 49% of the children reported one or more chronic GI complaints, 22% exhibited diarrhea, 26% suffered from constipation. Furthermore 13% of the parents reported their children to suffer from bloating and/or being gassy and while 10% of the parents reported vomiting or gastroesophageal reflux problems. Similar rates of GI symptoms were reported among pre‐school and school‐aged children. Inflammation of the gut was found in 6 of the 12 subjects who underwent endoscopic and colonoscopic evaluations, however clinical symptoms did not predict the results of the evaluation. GI dysfunction was significantly associated with sleep disorders and food intolerance, but not with irritability or aggressiveness. In summary, GI dysfunction was prevalent in this cohort of children with ASD, observations consistent with the reports of parents and other clinicians. We conclude that the GI dysfunction in ASD requires proper evaluation and treatment. Autism Res2014, 7: 501–506. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.